Factors contributing to milk yield and cost of goat milk production in Etawah district of Uttar Pradesh - DEOGHARE, P R (The Indian Journal of Animal Sciences, 2013)
The sub-optimal use of concentrates feed was a negative contributor to milk yield in medium. size (6-10 does) flocks. The green and dry fodder contributed significantly to the milk yield and was positive contributor in small-size (1.5 does) and large-size (above 10) flocks. The cost of rearing per goat per lactation varied in all the sizes of flocks. Taking cost A (cash cost and depreciation) into account, average cost per litre of goat milk production in small-size flockS was Re 0.97, whereas in medium-size and large-size flocks, it was Re 0.92 and Re 0.72 respectively. Overall cost of pro duel ion per litre of goat milk was Re 0.90.